Primary care providers’ role in newborn screening result notification for cystic fibrosis - Hayeems, Robin Z. (Can Fam Physician, 2021)
OBJECTIVE: To explore primary care providers’ (PCPs’) role in result notification for newborn screening (NBS) for cystic fibrosis (CF), given that expanded NBS has increased the number of positive screening test results, drawing attention to the role of PCPs in supporting families. DESIGN: Cross-sectional survey and qualitative interviews. SETTING: Ontario. PARTICIPANTS: Primary care providers (FPs, pediatricians, and midwives) who received a positive CF NBS result for an infant in their practice in the 6 months before the study. MAIN OUTCOME MEASURES: Whether the PCP notified the family of the initial positive CF screening result. RESULTS: Data from 321 PCP surveys (response rate of 51%) are reported, including 208 FPs, 68 pediatricians, and 45 midwives. Interviews were completed with 34 PCPs. Most (65%) surveyed PCPs reported notifying the infant’s family of the initial positive screening result; 81% agreed that they have an important role to play in NBS; and 88% said it was important for PCPs, rather than the NBS centre, to notify families of initial positive results. With support and information from NBS centres, 68% would be extremely or very confident in doing so; this dropped to 54% when reflecting on their recent reporting experience. More than half (58%) of all PCPs said written point-of-care information from the NBS centre was the most helpful format. Adjusted for relevant factors, written educational information was associated with a lower rate of notifying families than written plus verbal information (risk ratio of 0.79; 95% CI 0.69 to 0.92). In the interviews, PCPs emphasized the challenge of balancing required content knowledge with the desire for the news to come from a familiar provider. CONCLUSION: Most PCPs notify families of NBS results and value this role. These data are relevant as NBS programs and other genomic services expand and consider ways of keeping PCPs confident and actively involved.